THE IMPACT OF ISLAM ON SOCIO-POLITICAL STRUCTURE OF MANDARA SULTANATE: AN OVERVIEW - Mamman, Dani; Ibrahim, S. Y. (International Journal of Research -GRANTHAALAYAH, 2017)
The paper attempts to explore the impact of Islam on the socio-political structure of Mandara Sultanate. It gives insight into how Islam penetrated into the social and political structure of the Sultanate. The paper utilized mostly the secondary source of data and guided by the evolutionary theory. Among the findings are, deities and shrines played prominent role before the advent of Islam and today, festivals like Idil-Al-Fitr, Adha and Maulid-Nabiy replaced the harvest and rainfall festivals in the area. The paper concluded that Islam has impacted positively on the lives of the people in the area as Islam has become a dominant religion in the Mandara Sultanate in Borno State.